2013
DOI: 10.1097/mjt.0b013e31822831d8
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty Alone Versus Angioplasty and Stenting for Subclavian Artery Stenosis—A Systematic Review and Meta-analysis

Abstract: Subclavian artery stenosis has long been treated with great success with bypass surgery. Percutaneous intervention, often used in combination with stent placement, has come into vogue for the past few years as a safe and effective therapeutic modality. This study aimed to compare angioplasty alone with angioplasty followed by stent placement by combining available data. The objective of this study was to perform a review of the available literature to compare the efficacy of percutaneous transluminal angioplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…The results of the largest series suggested stenting as the treatment of choice in selected patients (4). In addition, Chatterjee et al (5) showed that stenting is significantly superior to angioplasty alone. We chose endovascular stenting approach for this patient.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the largest series suggested stenting as the treatment of choice in selected patients (4). In addition, Chatterjee et al (5) showed that stenting is significantly superior to angioplasty alone. We chose endovascular stenting approach for this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Subclavian artery stenosis was usually treated by surgical bypass surgery.In recent years, with the progress of interventional therapy equipment and technology, more and more patients have obtained satisfactory curative effect through interventional therapy.Interventional therapy mainly includes simple balloon dilatation and stent placement. Systematic reviews comparing the two treatments have shown that both have lower complication rates, and stent placement can better maintain the patency of blood vessels compared with simple balloon dilatation [1], but http://www.ijSciences.com Volume 9 -October 2020 (10)…”
Section: Discusssionmentioning
confidence: 99%
“…[6][7][8] Patients with symptomatic SAS should undergo revascularization, preferably with percutaneous transluminal angioplasty (PTA) as the first choice strategy. [9][10][11][12] This procedure has a low complication rate and a durable effect. [10][11][12] However, the impact of the PTA on specific SAS-related symptoms has not been evaluated in detail so far.…”
mentioning
confidence: 99%
“…[9][10][11][12] This procedure has a low complication rate and a durable effect. [10][11][12] However, the impact of the PTA on specific SAS-related symptoms has not been evaluated in detail so far.…”
mentioning
confidence: 99%